Contextual-Based E-Module Development Using Flip PDF Professional Application on Static Fluid - Aprilia, Aprilia; Rohmadi, Mukhlis; Syar, Nur Inayah (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
This research was based on students’ need analysis at SMAN 1 Kahayan Kuala and found that they faced difficulty learning physics, mainly static fluid material. There was a high need for an alternative teaching material that could be understood independently and more attractive and contained phenomena or occurrences related to the physic and the surrounding environment. Because of that, this research aims to know 1) the Procedure of the E-module based on contextual using PDF Flip Professional application on static fluid material. 2) Quality of E-module based on contextual using PDF Flip Professional application on static fluid material. 3) Students and teachers' responses on this e-module. This study used Research and Development in short R&D and 4D models. Phases were defined as design, development, and dissemination. But in dissemination phase was limited only to the research place. Results showed that 1) Procedure in developing an e-module involving students’ need analysis, designing the product, validating by design, material and learning experts and testing on small groups. 2) Quality of the e-module was tested through validity by media experts and was obtained at 92.95%, stated as very feasible. Next, validity from media experts was obtained at 95,9%, stated as very feasible. Then validity from learning experts was obtained 89,30% stated as very feasible. 3) Students’ response on e-module was obtained 95,09% stated as very good, and teachers’ response was obtained 92.8 stated as very good.